Handle decompositions of simply-connected five-manifolds. II - Shkol'nikov, Yu.A. (Український математичний журнал, 1993)
Handle decompositions of simply connected smooth or piecewise linear five-manifolds are considered. The basic notions and constructions necessary for proving further results are introduced. Розглядається розклад на ручки однозв’язних гладких або кусково-лінійних п’ятивимірних многовидів. Наведені основні поняття і конструкції, необхідні для одержання подальших результатів.